Clinical Characteristics and Mortality of Health-Care Workers With Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection in Mexico City. (28th September 2020) - Guerrero-Torres, Lorena; Caro-Vega, Yanink; Crabtree-Ramírez, Brenda; Sierra-Madero, Juan G
Abstract: Background: We evaluated the risk of death for health-care workers (HCW) with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in Mexico City during the coronavirus disease 2019 (COVID-19) pandemic, and describe the associated factors in hospitalized HCW, compared with non-HCW. Methods: We analyzed data from laboratory-confirmed SARS-CoV-2 cases registered from 27 February–31 August 2020 in Mexico City's public database. Individuals were classified as non-HCW or HCW (subcategorized as physicians, nurses, and other HCW). In hospitalized individuals, a multivariate logistic regression model was used to analyze the potential factors associated with death and compare mortality risks among groups. Results: A total of 125 665 patients were included. Of these, 13.1% were HCW (28% physicians, 38% nurses, and 34% other HCW). Compared with non-HCW, HCW were more frequently female, were younger, and had fewer comorbidities. Overall, 25 771 (20.5%) were treated as inpatients and 11 182 (8.9%) deaths were reported. Deaths in the total population (9.9% vs 1.9%, respectively; P  <  . 001) and in hospitalized patients (39.6% vs 19.3%, respectively; P  <  . 001) were significantly higher in non-HCW than in HCW. In hospitalized patients, using a multivariate model, the risk of death was lower in HCW in general (odds ratio [OR], 0.53) than in non-HCW, and the risks were also lower by specific occupation (OR for physicians, 0.60; OR for nurses, 0.29; OR for other HCW 0.61). Conclusions: HCW represent an important proportion of individuals with SARS-CoV-2 infection in Mexico City. While the mortality risk is lower in HCW compared to non-HCW, a high mortality rate in hospitalized patients was observed in this study. Among HCW, nurses had a lower risk of death compared to physicians and other HCW. Abstract : Among Mexico City patients with severe acute respiratory syndrome coronavirus 2 infection, 13.1% were health-care workers (HCW). There were significantly more deaths in non-HCW than HCW; the death risk remained higher in non-HCW after adjusting for age, sex, and comorbidities.